PENGARUH PROFITABILITAS, LEVERAGE DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Ruri Prahesti, 13.05.52.0230; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2017)
The purpose of this study is to examine the effect of profitability, leverage and dividend policy on corporate value. This research was conducted at a manufacturing company listed on the Indonesia Stock Exchange in 2013-2015. The population is all manufacturing companies listed on the BEI in 2013-2015. The sampling technique using purposive sampling with the study period 2013 to 2015. The analysis technique used is multiple linear regression with SPSS 21 program. As a requirement for the statistical program has been tested normality and the classical assumption that the results show the data is normally distributed and escaped from classic assumption test. The results showed that profitability has a significant positive effect on firm value. Leverage has a significant positive effect on firm value. While dividend policy has no effect on firm value.Keywords: Profitability, Leverage, Dividend Policy and Corporate Value